2013
DOI: 10.1002/ccd.24775
|View full text |Cite
|
Sign up to set email alerts
|

Two‐year outcomes after deployment of XIENCE V everolimus‐eluting stents in patients undergoing percutaneous coronary intervention of bifurcation lesions: A report from the SPIRIT V single arm study

Abstract: The aim of this analysis was to analyze outcomes of patients undergoing Xience V EES treatment of bifurcation lesions, a subset in which treatment is particularly challenging. The SPIRIT V Study provided an evaluation of the Xience V everolimus eluting stent (EES) performance in complex patient and lesion population. The SPIRIT V Single Arm Study enrolled 2700 patients with de novo coronary artery lesions suitable to be optimally treated with a maximum of four planned Xience V EES. Lesion evaluation was by vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Results of studies comparing one- with two-stenting techniques using second-generation DESs for coronary bifurcation lesions showed vast discrepancies. In the RESOLUTE ALL COMERS trial for 382 patients and the bifurcation substudy of the SPIRIT V for 492 patients, the rate of cardiovascular events was significantly higher in the two-stent technique, even with second-generation DESs [ 9 , 15 , 16 ]. In contrast, some studies reported favorable outcomes of the two-stenting technique compared to one-stent technique.…”
Section: Discussionmentioning
confidence: 99%
“…Results of studies comparing one- with two-stenting techniques using second-generation DESs for coronary bifurcation lesions showed vast discrepancies. In the RESOLUTE ALL COMERS trial for 382 patients and the bifurcation substudy of the SPIRIT V for 492 patients, the rate of cardiovascular events was significantly higher in the two-stent technique, even with second-generation DESs [ 9 , 15 , 16 ]. In contrast, some studies reported favorable outcomes of the two-stenting technique compared to one-stent technique.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were confirmed by a retrospective study in 319 patients, who were treated with Xience for TBL, showing favorable angiographic and 1-year clinical outcomes in patients treated with a 2-stent technique [30]. Despite the overall favorable outcome of bifurcation treatment with second-generation DES, there has been a higher incidence of periprocedural MI [13, 14, 27]. …”
Section: Discussionmentioning
confidence: 87%
“…17 Additionally, a report from the SPIRIT V single-arm study found that 30-day rates of death, myocardial infarction, and target vessel revascularization were higher in patients with bifurcation lesions PCI. 18 This increase in risk was found to persist well beyond 30 days, as Grundeken et al found increased risk of death, myocardial infarction, and target vessel revascularization at the 5-year time point. 19 When the results of these previous studies are compared alongside those of our study, it is clear that PCI of bifurcation lesions carries a much higher risk than non-bifurcation lesions (Figure 1).…”
Section: Discussionmentioning
confidence: 92%